Wm. Oland Bourne papers - Bourne, Wm. Oland (William Oland), 1819-1901.
Entries submitted in two contests sponsored by Bourne in which Union soldiers and sailors who lost their right arms by disability or amputation during the Civil War were invited to submit samples of their penmanship using their left hands, correspondence and broadsides concerning the contests, and photographs of the participants. Also includes Civil War reminiscences recorded by patients at the Central Park Hospital, a military hospital in New York City, and correspondence pertaining to slavery, economic conditions of the working man, operation of The Soldier's Friend, and the Workingmen's Democratic Republican Association.
Clergyman and journalist; chaplain at Central Park Hospital, New York City, during the Civil War, and editor of The Soldier's Friend.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Alphabetical listing of contest entrants and a list of photographs in the collectionavailable in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army -- History -- Civil War, 1861-1865.; United States. -- Navy -- History -- Civil War, 1861-1865.; Central Park Hospital; Workingmen's Democratic Republican Association; The soldier's friend; Amputees; Penmanship; People with disabilities; Slavery -- United States; United States -- Economic conditions; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil war, 1861-1865 -- Periodicals; United States -- Politics and government -- 19th century; Clergy; Journalists